Observing, tracking and analysing electrochemically induced atomic-scale structural changes of an individual Pt-Co nanoparticle as a fuel cell electrocatalyst by combining modified floating electrode and identical location electron microscopy. (20th August 2021) - Hrnjic, Armin; Kamšek, Ana Rebeka; Pavlišič, Andraž; Šala, Martin; Bele, Marjan; Moriau, Leonard; Gatalo, Matija; Ruiz-Zepeda, Francisco; Jovanovič, Primož; Hodnik, Nejc
Abstract: Upon exposure to an electrochemical environment, structural properties of nanoparticulate electrocatalysts at the atomic scale are not stagnant but rather dynamic. These have a direct effect on catalysts' performance via structure-property relationships. The active surface structure is constantly changing via complex phenomena dependant on their nature and reaction conditions. State-of-the-art transmission electron microscopy (TEM) can already provide us with atomically precise structures of individual nanoparticles, which are a key to exploring structure-property relations. However, with the analysis of random nanoparticles with unknown structural history, it is impossible to realise the exact structural alternation mechanisms. In order to study these phenomena operando, in-situ or quasi-in-situ methods need to be developed and used. In the present study, we highlight a recently introduced methodological approach named modified floating electrode (MFE), which enables the assessment of (i) proton exchange membrane fuel cell (PEMFC) cathode oxygen reduction reaction (ORR) at the industry-relevant current densities and (ii) atomic-level structural changes of the same nanoparticle, via identical location scanning electron microscopy (SEM) and TEM approach (IL-SEM and IL-TEM), in one measurement. Careful analysis and comparison of atomically resolved high-resolution scanning TEM (HR-STEM) images of the same nanoparticle before and after MFE measurements were conducted via homemade microscopy image analysis algorithms. We reveal structural changes on the atomic-scale of the industrial benchmark Pt-Co nanoalloy ORR electrocatalyst upon exposure to electrochemical activation and high ORR current densities. Observing and comparing the detailed structure and morphology of the same nanoparticle reveals atomic-scale processes such as particle anisotropic etching and redeposition, besides other processes such as particle necking, anti-necking, pore formation, particle movement, coalescence, etc. The understanding of the dynamics behind these changes is crucial for the interpretation of ORR electrocatalyst's activity and stability. Our bottom-up approach enables direct investigation of nanoparticles' structure-stability relationships.